DOSSIER MAKER CULTURE, TEACHER EDUCATION AND INCLUSIVE EDUCATION: INTERDISCIPLINARY DIALOGUES (Interdisciplinary Studies Journal, 2026)
This thematic dossier brings together studies that explore, from different theoretical and methodological perspectives, the relationships between maker culture, teacher education and inclusive education, articulating the challenges and possibilities of a school that reinvents itself in response to contemporary techno-social demands. By recognizing the centrality of learning by doing as a guiding principle of creative practices, this dossier shows that pedagogical innovation is not a methodological add-on, but a requirement of the very constitution of the educational space as a place of experimentation, authorship and the production of meaning.
Keywords: Presentation; Dossier; Maker Culture